Dampak Dan Efisiensi Program Padat Karya Sebagai Belanja Prioritas Untuk Mengentaskan Pengangguran: Kajian Literatur - Kumba Digdowiseiso; Aisyah Fitasari; Nastiyawati Nastiyawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Labor-intensive programs have become one of the policy instruments used by the Indonesian government in an effort to overcome unemployment and encourage economic growth. This study aims to analyze the impact and efficiency of labor-intensive programs as priority spending in alleviating unemployment, the indicators used in this study are the Open Unemployment Rate (TPT), government program spending, and the level of labor absorption. This research uses descriptive qualitative method with literature study through collecting information from various sources. The results show that labor-intensive programs have a positive impact in reducing the unemployment rate in Indonesia. The program is able to create new jobs especially in labor-intensive sectors such as infrastructure development and public works. In addition, the program also provides employment opportunities for vulnerable and marginalized groups of society, such as low-skilled workers and those living in economically disadvantaged areas. This contributes to reducing social inequality and increasing social inclusion. However, challenges remain, such as the potential for temporary employment that can lead to income instability and the lack of long-term job security. In addition, the program still lacks efficiency in budget realization for optimal resource allocation and maximum results. Keywords: Labor-intensive program; unemployment; PEN; efficiency; impact